2003
DOI: 10.1111/j.1745-4549.2003.tb00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Selected Drying Conditions and Storage Period and Quality of Walnut Selections

Abstract: Walnut selections were hulled at harvest time, and 3 and 5 days after harvest to determine the effects of hulling time on postharvest quality. Walnuts removed from their hulls were stored shelled and unshelled under ambient conditions after being dried at selected conditions. Among the tested hulling dates, the best results were obtained from the walnuts hulled at harvest time. At the end of the storage period, the least quality losses were determined in the walnuts dried in the sun. Generally, quality losses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
(3 reference statements)
1
7
0
Order By: Relevance
“…The highest MC was recorded at 12. months (5.57 %) in the DM, while the lowest value was recorded at 18. months (3.21 %) in the CG. Similar results were obtained in other studies and the moisture value decreased during storage (Koyuncu et al, 2003;Koc Güler et al, 2017). In another study, however, MC increased in hazelnuts maintained at ambient conditions for twelve months (Ghirardello et al, 2013).…”
Section: Moisture Contentsupporting
confidence: 90%
“…The highest MC was recorded at 12. months (5.57 %) in the DM, while the lowest value was recorded at 18. months (3.21 %) in the CG. Similar results were obtained in other studies and the moisture value decreased during storage (Koyuncu et al, 2003;Koc Güler et al, 2017). In another study, however, MC increased in hazelnuts maintained at ambient conditions for twelve months (Ghirardello et al, 2013).…”
Section: Moisture Contentsupporting
confidence: 90%
“…Olsen et al (1998) reported that as the hull and kernel mature simultaneously, the kernel was light colored. Similarly, Koyuncu et al (2003) stated that kernels which mature early in a warm climate and stay for a longer time in the hull darkened resulting from absorption of some acidic materials from the hull. In this study, because harvesting time coincided with formation of kernels for all cultivars in Cameli, the kernels displayed good quality (light colored).…”
Section: Results and Discussion The Effect Of Altitude On Fruit Qualitymentioning
confidence: 99%
“…Nuts harvested in the 2002 season were dried to approximately 10.5% w.b. in a drying room having an air conditioner system operating at the temperature of 30 ± 1C and relative humidity of 50% (Koyuncu et al 2003). The moisture contents of the shells (taken from 10 nuts of each cultivar) were determined using an oven set at 105 ± 1C for 24 h (three replicates).…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that drying process can highly preserve the quality of walnut kernels during prolonged storage by improving the bleaching efficiency and stabilizing the product mass (Koyuncu et al . ). Meanwhile, it is necessary to have knowledge on the thermal properties of the walnut kernels, including specific heat, thermal conductivity and thermal diffusivity, in order to effectively develop the processes and equipment needed in the drying and other thermal processes of the product.…”
Section: Introductionmentioning
confidence: 97%